Implementation issues of adaptive OFDM in mobile radio environment - Nor K., Noordin; Borhanuddin, Mohd Ali; Hadi, Habaebi (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/